Evaluation of Aromatic Boronic Acids as Ligands for Measuring Diabetes Markers on Carbon Nanotube Field-Effect Transistors. (28th February 2012) - Stefansson, Steingrimur; Stefansson, Lára A.; Chung, Suk-won; Ko, Kevin; Kwon, Hena H.; Ahn, Saeyoung Nate
Abstract : Biomolecular detections performed on carbon nanotube field-effect transistors (CNT-FETs) frequently use reactive pyrenes as an anchor to tether bioactive ligands to the hydrophobic nanotubes. In this paper, we explore the possibility of directly using bioactive aromatic compounds themselves as CNT-FET ligands. This would be an efficient way to functionalize CNT-FETs since many aromatic compounds bind avidly to nanotubes, and it would also ensure that ligand-binding molecules would be brought in close proximity to the nanotubes. Using a model system consisting of pyrene, phenanthrene, naphthalene, or phenyl boronic acids immobilized on CNT-FET wafers, we show that all are able to bind glycated human serum albumin (gHSA), which is an important diabetes marker. Pyrene boronic acid proved to bind CNTs with the greatest apparent affinity as measured by gHSA impedance. Interestingly, gHSA CNT-FET signal intensity, which is proportional to amount of protein bound, remained essentially unchanged for all the boronic acids tested.